Pengaruh Independensi, Pengalaman Kerja, Objektivitas, Dan Audit Fee Terhadap Kualitas Audit - Chandra Ariyanto, Denny; Goenawan Soedarsa, Herry (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Through independence, work experience and high objectivity are required from an auditor. These factors may affect the potential for auditors to earn audit fees for their offerings. However, there are still many events that question the audit conducted by the auditor. There was a case in Bandar Lampung where auditors dedicated fraud on behalf of Welly and Ahmad and made a public audit conducted. Therefore, this study was conducted to determine the effect of independence, professional experience, objectivity and audit fees on audit quality, using a questionnaire given to auditors at KAP in Bandar Lampung. Target sampling used as a research pattern approach, namely the distribution of 30 questionnaires. In studying the data, this test uses multiple linear regression analysis. The effect of the test shows that the variables of independence, expert experience, objectivity and audit fees have a significant positive effect on audit quality.